Management of Badhirya (Sensory Loss Of Hearing) with Ayurveda - Mohandudwe; Begum, Mamataj (International Research Journal of Ayurveda & Yoga, 2023)
Sensory neural hearing loss occurs when there is a problem in the sensory apparatus - cochlea (sensory) or in the pathways of conduction of nerve impulses to the brain. Sensory neural hearing loss can be Peripheral and Central (auditory pathway or cortex). It can be congenital or acquired. Congenital: present at birth, due to anomalies of inner ear or due to pre or perinatal factors. In present study we have discussed a case of a 12-year-old male child who came to OPD with complains of Sensory neural hearing Loss since childhood. Audiometry report showed Right ear moderate to profound mixed hearing loss Left ear - moderate to severe sensory neural hearing loss. First Ayurveda treatment of Sensory neural hearing loss with three sittings of Marsha Nasya from Anu Taila, 3 sittings of Karnapurana from Bilwadi Taila And Sarivadi Vati with the dose of 250mg thrice a day with luke warm water or milk for 1 month were given in a month and same procedure followed for 6 months. After that his hearing improved showing audiometric findings of Moderate hearing in both ear. After six months repeat Audiometry was done. Patient also felt better hearing in both ears. Decreased hearing due to Sensory neural hearing loss is result of Damage of hair cells, which can be managed with the help of Ayurveda treatment Marsha Nasya, Karnapurana with Rasayana treatment. Hearing loss to school going children is a very serious problem affecting their education, skills and social relationship with others.